Use of modified chitosan as bitumen modifier and its impact on rheological properties in bitumen modification - Kumar K.; Chand A.; Singh R.K.; Kumar A.; Chandra H.; Kumar P.; Joshi V.; Srivastava M. (My University, 2025)
Conventional bitumen is a viscoelastic material composed of asphaltene and maltene. It is prepared by air-blowing, but this approach makes the bitumen more brittle and susceptible to temperatures. To decrease the temperature susceptibility, synthetic polymers or additives are used to make polymer-modified bitumens. Polymer-modified bitumens have poor storage stability and phase separation and are costly. Chitosan has free amino and hydroxyl groups. Some studies showed that chitosan can be used as a bitumen emulsifier, increasing emulsion viscosity. This study describes the synthesis of O-carboxymethyl chitosan (OCMC) from chitosan, and the same was blended in base bitumen VG10 and VG30 to improve its constitutive properties. VG10 and VG30 grade bitumen were characterized for penetration, softening point, kinematic and absolute viscosity, and ductility. OCMC-modified bitumens were also characterized by their rheological and mechanical properties. OCMC was used in the concentration range of 0.5 to 4.5 wt%. The study revealed that using sulfur increases the ductility and penetration of modified bitumen with 1.5 wt% of OCMC and meets the specification of VG40-modified bitumen as per BIS specification IS:73:2013. The study showed that blending 1.5 wt% of OCMC in VG30 base bitumen enhances the complex modulus to 76,517 Pa (at 42 °C) with a minimum phase angle of 68.58° and meets the VG40 bitumen specification. Simultaneously, blending 1.5 wt% of OCMC in VG10 base bitumen enhances the complex modulus to 64,454 Pa with a minimum phase angle of 77.39° (at 42 °C) and meets the VG30 bitumen specification. Studies showed that using SBS in a small amount of 0.25 wt% along with modified chitosan improves the rutting resistance and shear modulus by more than 67 °C at 1.1 kPa. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.